Python GUI programming : a complete reference guide : develop responsive and powerful GUI applications with PyQt and Tkinter - Moore, Alan, 1961-; Harwani, B. M. (Packt Publishing, Limited, 2019)
This Learning Path guides you through every concept necessary to create fully functional GUI applications using PyQt and Tkinter with only a few lines of code. You'll learn to design and build GUIs that are functional, appealing, and user-friendly using the powerful combination of Python and its GUI frameworks.